2018
DOI: 10.1016/j.celrep.2018.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Visual Motion Processing in Macaque V2

Abstract: Graphical Abstract Highlights d DS neurons in a non-dorsal visual area (V2) were studied with map-guided recordings d V2 DS neurons exhibit features distinct from the DS neurons in the dorsal area MT d Clusters of V2 DS neurons form functional architectures sensitive to motion contrast d Response properties of V2 DS neurons are suitable for figureground segregation SUMMARY In the primate visual system, direction-selective (DS) neurons are critical for visual motion perception. While DS neurons in the dorsal vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 93 publications
(112 reference statements)
3
27
0
Order By: Relevance
“…Combining the results from the three experiments, we found that the early visual areas V1, V2, and V3 (V3v and V3d combined) respond to a position shift of the FoE defined by either motion or form cues. This is consistent with the findings of primate neurophysiology studies showing that these areas process both local motion and form information (Hubel and Wiesel, 1968;Mikami et al, 1986;Felleman and Van Essen, 1987;Levitt et al, 1994;Gegenfurtner et al, 1997;Hu et al, 2018). Research identifying the homology of primate areas V1, V2, and V3 in the human brain has been quite successful and shows that these areas in humans are organizationally and functionally analogous to those in macaques.…”
Section: Discussionsupporting
confidence: 88%
“…Combining the results from the three experiments, we found that the early visual areas V1, V2, and V3 (V3v and V3d combined) respond to a position shift of the FoE defined by either motion or form cues. This is consistent with the findings of primate neurophysiology studies showing that these areas process both local motion and form information (Hubel and Wiesel, 1968;Mikami et al, 1986;Felleman and Van Essen, 1987;Levitt et al, 1994;Gegenfurtner et al, 1997;Hu et al, 2018). Research identifying the homology of primate areas V1, V2, and V3 in the human brain has been quite successful and shows that these areas in humans are organizationally and functionally analogous to those in macaques.…”
Section: Discussionsupporting
confidence: 88%
“…This “real-to-illusory” higher order transformation must be mediated by the anatomical connectivity between V1 and V2. Specifically, we observe establishment of modality-specific higher order properties in different stripes of V2: (a) thin stripes : color representation in V1 blobs, which is dominated by red-green/blue-yellow axes, transforms to a multicolor map of hue columns in V2 (Conway, 2001; Xiao et al, 2003); (b) thin stripes : luminance encoding in V1 transforms to brightness encoding in V2 (Roe et al, 2005); (c) thick/pale stripes : encoding of simple contour orientation transforms to higher order cue-invariant orientation representation in V2 (Rasch et al, 2013); (d) thick stripes : simple motion direction detection transforms to the detection of coherent motion in V2 (useful for figure-ground segregation, Peterhans and von der Heydt) and to motion contrast defined borders (Hu et al, 2018); and (e) thick stripes : segregated representation of left and right eyes in V1 to maps of near-to-far binocular disparity columns in V2 (Chen et al, 2008, 2017). Touch : In a similar vein, in somatosensory cortex, integration of tactile pressure domains in area 3b (Friedman et al, 2004) are hypothesized to generate motion selectivity domains in area 1 (Pei et al, 2010; Wang et al, 2013; Roe et al, 2017).…”
Section: Columnar Motifsmentioning
confidence: 99%
“…Theoretical work shows that this sensitivity to small moving stimuli paired with insensitivity to wide-field, uniform motions is well suited to support segmentation of moving figures from their backgrounds 13,16–18 . However, direct behavioral evidence for this link is lacking, and even indirect neurophysiological evidence is limited 12,1921 . In fact, motion segregation could be accomplished by specialized processes not involving center-surround mechanisms 22 , with center-surround mechanisms playing a role in other visual processes, including redundancy reduction, input normalization, estimation of optic flow, heading direction, 3D shape-from-motion, and detection of edge discontinuities 2330 .…”
Section: Introductionmentioning
confidence: 99%